The cartel - Winslow, Don, 1953- (Winslow, Don, 1953- Power of the dog, 2015)
A sequel to "The Power of the Dog" finds a drug lord's prison transfer to Mexico upsetting a precarious balance of peace and forcing a DEA agent to come out of retirement to stop the ensuing violence.